Proceedings of the 39th International Conference on High Energy Physics — PoS(ICHEP2018) 2019
DOI: 10.22323/1.340.0538
|View full text |Cite
|
Sign up to set email alerts
|

Construction and performance tests of the COMET CDC

Abstract: A cylindrical drift chamber (CDC) has been constructed for the COMET Phase-I experiment where a lepton flavor violating process, the muon-to-electron conversion, is searched for with a sensitivity of 3 × 10 −15 at J-PARC. The CDC design was optimized to measure 105-MeV/c electrons as well as suppressing unwanted low-energy particles. In order to achieve required momentum resolution of 200 keV/c, the chamber is operated with a low-Z gas mixture of He (90%) and i-C 4 H 10 (10%) to mitigate the multiple scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…The nominal tension weights for the sense and field wires were set to be 50 and 80 g, which correspond to the gravitational sags of 50 and 120 µm at the center, respectively. We confirmed that the sag for the sense wires was controlled between 48 and 61 µm, and the sag differences between the sense and surrounding field wires are kept within less than 100 µm [7]. The 0.5-mm thick CFRP inner cylinder was installed after the wire stringing to close the gas volume of 2,084 litters.…”
Section: Pos(eps-hep2019)128supporting
confidence: 65%
“…The nominal tension weights for the sense and field wires were set to be 50 and 80 g, which correspond to the gravitational sags of 50 and 120 µm at the center, respectively. We confirmed that the sag for the sense wires was controlled between 48 and 61 µm, and the sag differences between the sense and surrounding field wires are kept within less than 100 µm [7]. The 0.5-mm thick CFRP inner cylinder was installed after the wire stringing to close the gas volume of 2,084 litters.…”
Section: Pos(eps-hep2019)128supporting
confidence: 65%
“…The 4986 sense and 14562 field wires were strung using gold-plated tungsten wires and unplated aluminum wires, respectively. Construction of the CDC has already been completed and performance tests with cosmic rays are well in progress [20,21] as shown in Fig. 6.…”
Section: Detectorsmentioning
confidence: 99%
“…The performance test using the cosmic rays is currently being worked on. As a preliminary result, a spatial resolution of 170 µm, which is enough to achieve the momentum resolution of 200 keV/c, has been obtained including the tracking uncertainty [5].…”
Section: Cylindrical Drift Chambermentioning
confidence: 99%